Try this

Algebra Level 4

If a , b , c a,b,c are distinct and p ( x ) p(x) is a polynomial in x x which leaves a remainder a , b , c a,b,c on division by ( x a ) , ( x b ) , ( x c ) (x-a),(x-b),(x-c) respectively.Find the remainder obtained on division of p ( x ) p(x) by ( x a ) ( x b ) ( x c ) (x-a)(x-b)(x-c)

x x 2 2 x 2 x^2 0 0 1 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Surya Prakash
Aug 14, 2015

Let P ( x ) = Q ( x ) ( x a ) ( x b ) ( x c ) + R ( x ) P(x) = Q(x) (x-a)(x-b)(x-c) + R(x)

Since the degree of divisor is 3 3 . So, the degree of R(x) is atmost 2 2 .

So, Let R ( x ) = p x 2 + q x + r R(x) = px^{2} + qx +r .

So, P ( a ) = p a 2 + q a + r P(a) = pa^2 + qa + r , P ( b ) = p b 2 + q b + r P(b) = pb^2 + qb + r and P ( c ) = p c 2 + q c + r P(c) = pc^2 + qc + r .

But, P ( a ) = a , P ( b ) = b , P ( c ) = c P(a) = a, P(b) = b, P(c) =c

So, a = p a 2 + q a + r a = pa^2 + qa + r , b = p b 2 + q b + r b = pb^2 + qb + r and c = p c 2 + q c + r c = pc^2 + qc + r .

It implies that a b = p ( a 2 b 2 ) + q ( a b ) a-b = p(a^2 - b^2) +q(a-b) and b c = p ( b 2 c 2 ) + q ( b c ) b-c = p(b^2 - c^2) +q(b-c)

So, p ( a + b ) + q = 1 p(a+b) +q = 1 and p ( b + c ) + q = 1 p(b+c) +q = 1 .

Subtracting the above equations,

We get p ( a c ) = 0 p(a-c) = 0 . But a c a \neq c .

So, p = 0 p = 0

So, it will imply that q = 1 q = 1 and r = 0 r=0 ( But How? Try yourselves )

So, R ( x ) = x \boxed{R(x) = x} .

Moderator note:

Simple standard approach via the Remainder-Factor Theorem.

Best standard solution

Sai Ram - 5 years, 10 months ago
Sai Ram
Aug 15, 2015

Let P ( x ) = Q ( x ) ( x a ) ( x b ) ( x c ) + R ( x ) P(x)=Q(x)(x-a)(x-b)(x-c)+R(x)

Since the degree of the divisor is 3. 3. So, the degree of R ( x ) R(x) is 2. 2.

Let R ( x ) R(x) be l x 2 + m x + n . lx^2+mx+n.

Now, P ( x ) = Q ( x ) ( x a ) ( x b ) ( x c ) + ( l x 2 + m x + n ) . P(x)=Q(x)(x-a)(x-b)(x-c)+(lx^2+mx+n).

Given that

P ( a ) = a a = l a 2 + m a + n P(a)=a \Rightarrow a=la^2+ma+n

P ( b ) = b b = l b 2 + m b + n P(b)=b \Rightarrow b=lb^2+mb+n

P ( c ) = c c = l c 2 + m l + n P(c)=c \Rightarrow c=lc^2+ml+n

( a b ) = l a 2 l b 2 + m a m b ( a b ) = l ( a + b ) ( a b ) + m ( a b ) (a-b)=la^2-lb^2+ma-mb \Rightarrow (a-b)=l(a+b)(a-b)+m(a-b)

l ( a + b ) + m = 1............................... 1 \Rightarrow l(a+b)+m =1 ............................ ... \boxed{1}

Similarly , ( b c ) = l b 2 l c 2 + m b m c ( b c ) = l ( b c ) ( b + c ) + m ( b c ) (b-c)=lb^2-lc^2+mb-mc \Rightarrow (b-c)=l(b-c)(b+c)+m(b-c)

l ( b + c ) + m = 1............................... 2 \Rightarrow l(b+c)+m = 1 ...............................\boxed{2}

Similarly, ( a c ) = l a 2 l c 2 + m a m c ( a c ) = l ( a c ) ( a + c + m ( a c ) ) (a-c)=la^2-lc^2+ma-mc \Rightarrow (a-c)=l(a-c)(a+c+m(a-c))

l ( a + c ) + m = 1............................... 3 \Rightarrow l(a+c)+m =1 ...............................\boxed{3}

Solving 1 , 2 \boxed{1} , \boxed{2} ,we get,

l ( a + b ) l ( b + c ) + m m = 0. l(a+b) -l(b+c)+m-m = 0.

l a + l b l b l c = 0. la+lb-lb-lc=0.

l ( a c ) = 0. l(a-c)=0.

But, a c l = 0 a \neq c \Rightarrow \boxed{ l=0}

Substituting l = 0 l=0 in 1 , \boxed{1}, we get ,

0 ( a + c ) + m = 1 m = 1 0(a+c)+m=1 \Rightarrow \boxed{m=1}

Substituting l , m l,m in P ( a ) , P(a), we get ,

a = 0 ( a 2 ) + 1 ( a ) + n n = 0. a=0(a^2)+1(a)+n \Rightarrow \boxed{n=0.}

Now, R ( x ) = l x 2 + m x + n = 0 ( x 2 ) + 1 ( x ) + 0 = x R(x)=lx^2+mx+n = 0(x^2)+1(x)+0 = \boxed{x}

Therefore the remainder is x . x.

Great work.Upvoted

Rama Devi - 5 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...